Свойства эритроцитов, отмытых после замораживания-оттаивания в среде с сахарозой и 1,2-пропандиолом - Рамазанов, В.В.; Воловельська, Є.Л.; Ніпот, О.Є.; Єршов, С.С.; Єршова, Н.А.; Руденко, С.В.; Бондаренко, В.А. (Вісник Української медичної стоматологічної академії "Актуальні проблеми сучасної медицини", 2018, т.18, выпуск 1(61), стр. 188-192, 2018)
Трансфузия эритроцитов после длительного гипотермического хранения (ГТХ) не всегда нормализует гемодинамику и может приводить к развитию посттрансфузионного системного воспаления. Замораживание и хранение эритроцитов в жидком азоте (–196°С) позволит исключить длительное ГТХ и, возможно, предупредить воспалительный процесс. В работе показано, что замораживание эритроцитов в среде, содержащей 1,2-ПД (22%), сахарозу (10%) и невысокую концентрацию NaCl (0,27%) обеспечивает сохранение осмотических и морфологических характеристик. Кроме того, сохраняется клеточный АТФ на уровне 77%, который необходим для осуществления эритроцитами функции регуляции сосудистого тонуса. Эффективность комбинированного криконсерванта, вероятно, связана с тем, что на стадии замораживания проникающий криопротектор (1,2-ПД) противодействует «критическому» сжатию клеток, значительный вклад в которое вносит концентрирование сахарозы. Вместе с тем, при оттаивании сахароза предотвращает чрезмерное увеличение объема клеток. В сумме происходит ослабление гипертонического и осмотического стресса на клетки, что обуславливает сохранение осмотических характеристик и АТФ. -----------------------------------------------------------------------------------------------------------------------------------------------------Transfusion of red blood sells freeze-preserved for a long period of time does not always result in normal haemodynamics and can cause post-transfusion systemic inflammation. These negative consequences are associated with a decrease in the level of ATP and 2,3-DPG erythrocytes freeze-preserved for long period of time. Massive transfusion of such processed erythrocytes can lead to a fatal outcome associated with the development of post-transfusion systemic inflammation in severe trauma and heart surgery. This inflammation is initiated by iron ions, which are released upon destruction of freeze-preserved erythrocytes in macrophages, followed by stimulation of the synthesis of pro-inflammatory cytokines. Freezing and storing erythrocytes in liquid nitrogen (–196 ° C) enables to prevent serious side effects, including the development of inflammation. However, even during autotransfusion of erythrocytes after their freezing in a medium with glycerol followed for a short period time (up to 7 days), the post-transfusion value of cell survival within 24 hours is 70-75%. Destruction of erythrocytes after the transfusion is determined by their damage during freezing, according to literature data. The solution of the problem of preventing cell damage during freezing may consist in the development of combined cryo-preservatives, containing a significant fraction of the nonpenetrating cryoprotectant. It was found out earlier, that the rapid freezing of erythrocytes in a medium containing non-penetrating and penetrating protective components ensures the preservation of cell resistance to the action of osmotic stress during rapid thawing. Moreover, erythrocytes frozen in these media differ slightly in osmotic and morphological characteristics of intact cells. This paper has shown that the freezing of erythrocytes in a medium containing sucrose (10%) and 1,2-propanediol (1,2-PD, 22%) with a low NaCl content (0,27%) ensures the preservation of the osmotic and morphological characteristics of cells. In addition, cellular ATP is maintained at a level of 77% of control that is necessary for the implementation of red blood cells regulation of vascular tone. It can be assumed, the effectiveness of the combined cryo-protectants is due to the fact that in the freezing stage the penetrating cryoprotectant (1,2-PD) counteracts the "critical" cell contraction, a significant contribution to which is made by the concentration of sucrose. At the same time, when thawing sucrose prevents an excessive increase in the volume of cells. In sum, there is weakening of hypertonic and osmotic stress on cells that causes the preservation of osmotic and morphological characteristics.
PROPERTY OF RED BLOOD CELLS WASHED AFTER QUICK FREEZING-THAWING IN MEDIUM WITH SUCROSE AND 1,2- PROPANЕDIOL
Рамазанов ВВ, Воловельская ЕЛ, Нипот ЕЕ, Ершов СС, Ершова НА, Руденко СВ, Бондаренко ВА. Свойства эритроцитов, отмытых после замораживания-оттаивания в среде с сахарозой и 1,2-пропандиолом. Вісник Української медичної стоматологічної академії "Актуальні проблеми сучасної медицини". 2018;18 (1): с.188-192
Keywords: эритроциты; АТФ; замораживание; морфология